Exploring the potential of artificial intelligence in chemical engineering education / Nurul Asyikin Md Zaki, Syafiza Abd Hashib and Ummi Kalthum Ibrahim - Md Zaki, Nurul Asyikin; Abd Hashib, Syafiza; Ibrahim, Ummi Kalthum (Universiti Teknologi MARA, Kedah, 2024)
Chemical engineering education, traditionally grounded in rigorous theoretical instruction and hands-on laboratory experiences, stands on the edge of a transformative shift with the advent of Generative Artificial Intelligence (AI). This manuscript explores the potential of generative AI as a dynamic tool capable of producing innovative content tailored to enhance the learning experience in chemical engineering. This manuscript explores the integration of AI in education and its preliminary applications in creating complex simulations, diverse problem sets, and virtual experiments for chemical engineering students. Generative AI holds immense potential to reshape chemical engineering education, paving the way for a future that not only delivers education, but also dynamically crafts it to suit the unique needs of each learner. This work serves as a roadmap for educators, researchers, and policymakers eager to harness the power of AI to shape the next generation of chemical engineers.